Nurturing Islamic Morality Through Stimulus-Response Learning: Evidence from a Quasi-Experiment in Indonesian Elementary Schools - Muthmainna, Aqila; Febrianto, Andre; Harto, Kasinyo; Suryana, Ermis; Sirozi, Muhammad (Universitas Muhammadiyah Surakarta, 2025)
This study aims to determine the effectiveness of behaviouristic approach in learning Islamic Religious Education (PAI) on moral formation of elementary school students. The study used a quasi-experimental design with a pretest-posttest control group model. The subjects consisted of 50 fifth grade students of SDN 141 Palembang who were divided into two groups: experimental (n=25) and control (n=25). The experimental group received PAI learning with a behaviouristic approach based on positive reinforcement such as praise and symbolic rewards for 8 weeks, while the control group received conventional learning. The research instruments were Likert scale questionnaires and observation sheets. The results of the independent t-test analysis showed that the experimental group experienced a significant increase in the aspects of discipline, honesty, and politeness with an average score of 83.44 compared to the control group with an average score of 71.36. Observations also showed that the consistency of religious behaviour was higher in the experimental group. Thus, the behaviouristic approach has the potential to improve students' moral formation if supported by consistent reinforcement and a conducive learning environment.